PENGARUH PENGELUARAN PEMERINTAH,PERTUMBUHAN EKONOMI DAN DESENTRALISASI FISKAL TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI ACEH - Putri, Hesty Pradita; Ichsan, Ichsan (LPPM UNIMAL, 2023)
This study aims to analyze the effect of government spending, economic growth and fiscal decentralization on the Human Development Index (HDI) in Aceh Province. The data used in this research is secondary data for 2014-2021 accessed from www.bps.go.id. The data analysis method used is panel data regression analysis using Eviews 10 software. The results show that government spending and economic growth partially haveno a significant effect on HDI in Aceh Province. Meanwhile, fiscal decentralization has a positive and significant effect on IHDin Aceh Province. Simultaneously, government spending, economic growth and fiscal decentralization have a positive and significant effect on HDI in Aceh Province. Government Aceh is expected to be more consistent and intensive in increasing the HDI through programs related to economic, health and education aspects.